Manajemen Operasioanl Strategi Sebagai Upaya Pengendalian Mutu Pelayanan Di Rumah Sakit Khusus Bedah Hasta Husada - Edy Wahyudi; Andy Endra Krisna (STIKes Ibnu Sina Ajibarang, 2024)
Hospitals have various operational activities, including production, marketing and financial recording activities. The concept of operations management is very important for managing hospital operations. Globalization has had an impact on changes in the strategic environment. Globalization has triggered the emergence of competition in various fields. With this competition, every hospital strives and is required to improve the quality and quality of services both in terms of methods and technology used to support services. Quality control must be implemented and maintained properly as a value that has an impact on all aspects of the hospital, one of which is increasing turnover from the business side. A quality management system is an arrangement that ensures the achievement of planned quality goals and objectives in hospital services. To carry out quality hospital services, it is necessary to implement good operational management as a means of supporting high quality hospital services that have value in the point of view of the community. This phenomenon exists, therefore the authors use the scoping review method as a research method. This aims to review previous literature that has explored the quality of hospital services and the implementation of operational management as a means of quality control in hospitals.